EARTHQUAKE HAZARD ASSESSMENT IN CENTER OF JAKARTA BASED ON SEISMICITY DATA, DEM, SLOPE, FAULT, AND GIS - Ahmad Pratama Putra (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2019)
The newest finding in 2016 about Baribis thrust, if it is pulled straight from Cibatu to Tangerang, it is roughly found that this fault passes through several sub-districts in Jakarta. Meanwhile, Center of Jakarta as the capital city, many governmental, economic, and business activities are conducted in this area. And also Geographic Information System (GIS) techniques are commonly used for monitoring and damage assessment for many natural and geological hazards. The present study, GIS techniques have been used to generate various thematic layers to assess earthquake hazard with a suitable numerical ranking scheme, mesh processing, and spatial data integration. The results also show that the proposed model provides reasonable earthquake potential index (EPI) from elevation, slope, magnitude, active fault, and epicentre parameters compared to the peak ground acceleration (PGA) in Center of Jakarta. The result of the EPI map explained just a little area in Center of Jakarta has very high EPI. Very high EPI area mostly in southeastern part in the study area, exactly in Menteng sub-district. And also illustrated, spatially in the more northward area indicate the smaller of the EPI in the study area. EPI resulted from the calculation of surface parameter have the same indication or same trend with PGA.